2015
DOI: 10.1111/apa.12884
|View full text |Cite
|
Sign up to set email alerts
|

The quick and easy Mongolian Rapid Baby Scale shows good concurrent validity and sensitivity

Abstract: Our newly developed tool takes only 15 min to complete and is easy to administer. It demonstrated good concurrent validity and sensitivity for the screening of developmental status in young children. This innovative tool will be useful to identify children who may benefit from early interventions in Mongolia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The primary outcome in this study was child development. Child development was evaluated using the Mongolian Rapid Baby Scale (MORBAS) [ 13 ]. MORBAS is an easy to use rapid screening tool for healthcare providers and parents to evaluate risk of developmental delay in young children.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary outcome in this study was child development. Child development was evaluated using the Mongolian Rapid Baby Scale (MORBAS) [ 13 ]. MORBAS is an easy to use rapid screening tool for healthcare providers and parents to evaluate risk of developmental delay in young children.…”
Section: Methodsmentioning
confidence: 99%
“…The tool is comprised of seven developmental domains on gross motor, fine motor, cognitive, expressive language, receptive language, social-emotional, and adaptive-behavior. A validation study conducted by comparing the MORBAS with an international gold standard, Bayley-III showed good concurrent, face and content validity [ 13 ]. In current study, MORBAS was utilized by healthcare providers at the study hospital to assess risk of developmental delay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After further review and application of selection criteria, 18 articles were selected for inclusion in study. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] A PRISMA flow diagram has been prepared to illustrate the study selection process (as shown in figure 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…The tool is suitable for children aged 0-42 months. 47 In a study conducted in Mongolia, MORBAS was administered in a convenience sample of 150 Mongolian children aged 0-42 months and thus validated against the Bayley Scales of Infant and Toddler Development-III (BSID-III). With sensitivity 81.8% and specificity 52.3%, 47 MORBAS could be useful in the long run to screen out children for early intervention and rehabilitation.…”
Section: Lucknow Development Screenmentioning
confidence: 99%